Reduction in Current THD of Grid Parallel Inverters Using Randomized PR Control - S. Salimin; S. A. Zulkifli; M. Armstrong (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
In grid connected system, unity power factor current injection into the grid is vital. This can be achieved by choosing the right inverter topology, passive filter components, current controllers, and PWM switching scheme. This paper compares the output current harmonics profile between when using the conventional proportional resonant (PR) current controller and when using the modified PR current controller. By applying the latter technique, via experimental validation using TMS320F2812, the THD of the injected grid current in a parallel connected inverters system is improved.